Upaya Guru Bk Dalam Meningkatkan Pemahaman Tentang Good Personality di MAN 1 Kota Bukittinggi - Latifa Khairani; Elviana Elviana; Albahri Albahri (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
In connection with technological developments which also have a negative impact on users, most of whom are the successors of the nation itself. Currently, many of the nation's successors are seen starting to have bad personalities, such as filling their free time with gadgets rather than other useful things, so that the attitudes they produce are less in line with the normal characteristics of the nation's children. The purpose of this research is to see how guidance and counseling teachers' efforts are in increasing understanding of good personality at MAN 1 Bukittinggi City. Data has been collected using observation and interview methods. The method used in this research is a descriptive qualitative method. There are several efforts made by BK teachers to increase understanding of good personality in this research, namely 1) Providing material about good personality through one of the guidance and counseling services such as classical guidance, 2) Providing support- positive support for students' daily activities so as to create self-confidence in individuals to have a good personality, both at school and outside school, 3) If you experience problems in your daily life that require counseling, they will be maximized with individual counseling or counselling group.